Multilingualism in Canadian schools: Myths, realities and possibilities - Duff, Patricia A. (Canadian Journal of Applied Linguistics, 2007)
Bilingualism and multiculturalism have for four decades been official ideologies and policies in Canada but, as is often the case, the implementation and outcomes of such government policies nationally are less impressive than the rhetoric would suggest. This article reviews the political, theoretical and demographic contexts justifying support for the learning and use of additional languages in contemporary Canadian society and schools, and summarizes research demonstrating that bilingualism and multilingualism are indeed cognitively, socially, and linguistically advantageous for children (and adults), as well as for society. The five studies in this special issue are then previewed with respect to the following themes that run across them: (1) the potential for bilingual synergies and transformations in language awareness activities and crosslinguistic knowledge construction; (2) the role of multiliteracies and multimodality in mediated learning; and (3) the interplay of positioning, identity, and agency in language learning by immigrant youth. The article concludes that more Canadian schools and educators must, like the researchers in this volume, find ways to embrace and build upon students’ prior knowledge, their creativity, their collaborative problem-solving skills, their potential for mastering and manipulating multiple, multilingual semiotic tools, and their desire for inclusion and integration in productive, engaging learning communities.